Nebular and Nonthermal Radio Emissions for Young Stellar Populations with PARSEC v1.2s - Ikechukwu A. Obi; Pius N. Okeke; Bonaventure I. Okere (The Astrophysical Journal)
In this paper, we compute, by means of the recently and thoroughly updated PARSE v1.2 s database of stellar nonrotating evolutionary tracks, the integrated stellar spectra, the ionizing photon budget, and the supernovae rates of young simple stellar populations (SSPs), for five metallicities between 0.0001 and 0.02 and four choices of stellar initial mass function (IMF) upper mass limits between 40 M _⊙ and 350 M _⊙ . Using the photo-ionization code CLOUDY , we compute, at this same range of metallicities and limits, the intensities of some selected recombination and collisionally excited lines as a function of the age of the SSP. We account for the electron temperature dependence on IMF upper mass limit and metallicity while computing the thermal radio emission component, and also accounted for recent advances in core-collapse supernova explosion models while computing the nonthermal radio emission component. We self-consistently add the emission lines, nebular continuum, and nonthermal radio emission to the original SSP integrated photospheric spectra. Finally, from the resulting new suite of SSPs, we provide a consistent set of analytical relations between star formation rate (SFR) and ultraviolet, optical, and thermal radio luminosities that can be used to convert attenuation-corrected and dust-unaffected luminosities to SFR estimates. In a forthcoming paper, we will use our new SSP libraries as input to the state-of-the-art radiative transfer model GRA phites and SIL icates to test the overall performance of these SSPs in reproducing the observed spectral energy distribution of young star-forming galaxies.